An Essay on Biological Systems - Inoue, S (Iyo denshi to seitai kogaku, 1974)
An attempt to know the principle of control in the living systems by investigators in broad fields of nonbiological disciplines may give rise to the following expectation. The present-day technological civilization has urged every unit component and every unit process of our society to organize into certain purpose-pursuing systems, which have never existed before. Such huge artificial systems have brought about a tremendous development on one hand, but an unexpected transitional chaos on the other, which covers a world-wide range of disturbances to the harmony in our biosphere. Meanwhile, a biological organism exists as a totality, exhibiting a beautiful harmony not only with other external components but also with its own internal components. Consequently, the control principle governing the biological systems may give some valuable suggestions for the construction and well maintenance of artificial systems, through reorganizing our view of value. On the basis of such presupposition, discussions extend to how we can categorize living organisms into systems from phylogenetical, ontogenetical, distributional, morphological, biochemical, physiological, behavioral standpoints and so forth, referring to the integrative role played by the neuroendocrine control system. Then some characteristics of biological systems such as the a posteriori nature which is related to adaptability, individuality and feedback mechanism, the reproductivity and reutility associated with chain-relations and cyclicity, the variety and individual differences, and the incompleteness and nonlinearity related to dynamic stability, are described in comparison with artificial systems. The methodology applied to the analysis and synthesis of biological performances are also briefly reviewed. Finally, the difference between the status of our-recognition and the initial expectation is clarified together with some optimistic encouragement based on an analogy with evolutional history of the living organisms.